Alih Teknologi Pengolahan Pasca Panen Kopi Arabica Karo Dalam Peningkatan Produksi dan Pengemasan Menuju standarisasi Ekspor - Destiadi, Rezha; Hasibuan, Annalisa Sonaria; Muhammad Anhar Pulungan; Nofriadi; Chan, Andi Supriadi (LPPM ITEBA, 2025)
Plantation commodities are one of the largest contributors to Indonesia's foreign exchange. In 2019, the total value of plantation exports reached IDR 359.14 trillion. As the fourth largest producer of coffee beans in the world, Indonesia places coffee as one of its leading plantation commodities. In 2019 until now, the value of coffee exports ranks as the fourth largest commodity in Indonesia. If this program's sustainability plan goes well, it is hoped that partners will be able to utilize the innovative technology that has been provided independently, increase harvest yields and be able to sell and distribute the harvest and even export to Malaysia. The activity will be carried out until December 2024. This activity will be carried out in Kab. Karo. The concept of knowledge and technology transfer carried out in this activity is divided into three stages. The first stage is the preparation of activities, the stage of implementation of coaching activities and evaluation of activities.Based on the results of visits and interactions with partners, it shows that there are 3 problems as previously described. then the programs and solutions offered to solve the problems faced by these partners are:The problem faced by Megara Coffee partners is that the very small sales results are caused by farmers directly selling the coffee logs to middlemen, because coffee processing activities are expensive.Megara Coffee and Warung Dayac do not yet have adequate processing technology and have done it semi-conventionally for post-harvest activities, namely with the help of a small huller machine with a capacity of 10 kg/hour. Increase in partner production up to 100% and partner product packaging becomes export standardization.